21st Century Leadership Skills, Technological Competence and School Performance - Gardose, Rences; Gardose, Nerces (Journal of Interdisciplinary Perspectives, 2024)
This study ascertained the level of 21st-century leadership skills of school heads, the technological competence of teachers, and school performance. The descriptive-correlational research method was employed in this study. The main respondents of the study comprised 9 school heads and 45 elementary school teachers. Results revealed that school heads and teachers exhibit similar trends in their profiles, sharing commonalities in sex, age, and educational attainment. Most school heads boast over two decades of service, contrasting with teachers who are relatively new to the profession. Despite demographic differences, school heads display very satisfactory leadership skills across all indicators, showcasing consistency regardless of factors like sex, educational background, or length of service. Conversely, while teachers generally demonstrate proficiency in technology, they require further development in areas such as productivity, professional practice, and addressing social, legal, and human issues. Nevertheless, their technological competence remains consistent across different demographic profiles, indicating comparable proficiency. Assessments of both office and learners' performances range from very satisfactory to outstanding. Interestingly, there is no direct correlation observed between the leadership skills of school heads, the technological competence of teachers, and overall school performance, suggesting a complex interplay of factors influencing educational outcomes. The findings of this study can contribute to discussions to improve the quality of education.